The Influence of Curriculum Management on the Integration of the National Curriculum in Modern Islamic Boarding Schools - Hasbullah, Hasbullah; Ramadan, Syahru (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to empirically examine the effect of curriculum management on the level of integration of the national curriculum in a modern pesantren environment, especially at Pondok Pesantren Al Junaidiyah Biru, Bone Regency. The background of this study is the urgency to harmonize the Islamic values-based pesantren curriculum with the national curriculum standards as a response to the competency demands of the 21st century. This study used a quantitative approach with a correlational survey design. The entire population of 38 permanent teachers was used as respondents through the census technique. Data were collected using a Likert-scale questionnaire instrument that had been tested for validity and reliability. Data analysis was conducted through classical assumption tests (normality and linearity), Pearson correlation, and simple linear regression. The results showed a positive and significant relationship between curriculum management and national curriculum integration, with a correlation coefficient of r = 0.572 and a regression coefficient of 0.307 (p < 0.05). The coefficient of determination (R²) of 0.327 indicates that 32.7% of the variation in curriculum integration is explained by the quality of curriculum management. The findings corroborate Mintzberg and Ornstein's educational management theory and demonstrate the importance of planning, organizing, and evaluating curriculum systematically and contextually. This research makes an important contribution to the development of Islamic education management theory as well as a practical foothold for formulating pesantren curriculum policies to be more adaptive to social, cultural, and educational globalization changes.